THE OPEN VOCATIONAL TRAINING: MANAGERIAL AND PEDAGOGICAL ASPECTS - Anishchenko, Volodymyr (Professional Pedagogics, 2014)
The article deals with the legal framework, organizational and pedagogical of the modular-basedflexible technology of the open vocational training. Ukraine has conducted research on the use oftechnology in open vocational training. As a result of these studies was defined a clear picture ofqualitatively new opportunities for technical training of production personnel of enterprises.Open training – a synthesis of day, evening, part-time and distance learning, which is based on amodular methodology of the International Labour Organization.Development of a modular training program is based on detailed studies of the structural parts of aprofession or type of work in order to determine the necessary knowledge, skills and professionalcompetence. The program comes with a specially designed training and teaching materials. Widelyused in electronic materials and laser media. For the organization of open vocational training usingspecial resource centers.It is determined that one of the key characteristics of open vocational training is a high degree ofindependence of the student, which becоme the center of the learning process. The learning processchanges itself as compared to the traditional one. Teacher’s role also changes.On the basis of previous studies developed concept of open vocational training and the "Regulations onOpen vocational training."It was found that the use of technology of the open vocational training provides high quality training,expanding the field of educational services, facilitates access to learning.
Keywords: accessibility; flexibility; modularity; distance; resource base; quality of vocational training; vocational; skills; competency